New Generation of Fixture-Abutment Connection Combining Soft Tissue Design and Vertical Screw-Retained Restoration: 1-Year Clinical, Aesthetics and Radiographic Preliminary Evaluation - Francesco Mattia Ceruso; Irene Ieria; Mirko Martelli; Aurea I. Lumbau; Erta Xhanari; Marco Gargari (MDPI AG, 2021)
Implant design factors and the abutment connection are correlated with crestal bone stability. The aim of the present study was to evaluate a new type of screw-retained prostheses delivered on tissue-level implants with conical external vertical seal and internal hexagon connection. Implants 4.25 mm in diameter and 10 mm in length (Prama, Sweden and Martina) were placed in partially edentulous patients needing at least one implant in the healed site, having sufficient bone volume. The implant neck was positioned above the bone crest. A healing abutment was placed according to a one-stage approach. Outcome measures were implant and prosthesis survival rate, any complications, marginal bone loss (MBL), periodontal parameters, and pink esthetic score (PES). Overall, 13 patients (4 women and 9 men; mean age 50 ± 22 years) with the same number of implants were treated and followed for one year after loading. At the 12-month follow up, no implant and no prosthesis failed, and no complications were experienced. The mean MBL experienced at the one year follow-up was 0.65 ± 0.48 mm. One year after loading, 2 out of 13 implants present bleeding on probing (15.4%), 4 out of 13 patients presented with plaque at the one year of follow-up (30.8%) and the PES was 10.5 ± 2.3 mm. Within the limitations of the present study, the analyzed implants seem to be a viable treatment option for the rehabilitation of a single tooth gap.